Asylum Seekers, New Businesses, and Job Creation - Zohal Hessami; Sebastian Schirner; Clara Wobbe (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
How do asylum seekers affect host-country economies from a supply and demand perspective? What share of such immigration shocks is absorbed by existing vs. new businesses? To study these questions, we combine exclusive business registration and asylum seeker data for the universe of German districts over 2007-2021. We address endogeneity in asylum seeker allocation by exploiting rule-based allocation quotas as an instrument. A one SD treatment (10 asylum seekers/1,000 inhabitants) leads to 0.7 new businesses (7.9% increase) including 2.7 full-time jobs per 1,000 inhabitants. A sector-level analysis suggests that the founding of new businesses is both supply- (additional workforce) and demand-driven (need for basic goods/services), while the demand effect kicks in first. District-level employment data shows that total job creation is about four times larger, suggesting that 75% of the immigration shock is absorbed by existing businesses.
Keywords: F22; J20; L26; 330; asylum seekers; business registrations; host-country economy